1996
DOI: 10.1212/wnl.47.5.1162
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after stroke followed by surgical closure of patent foramen ovale

Abstract: Our study of 30 selected stroke patients with surgical suture of PFO showed a stroke recurrence rate of 0% and no significant complication. Residual right-to-left shunting may be avoided by double continuous suture of the PFO. In the absence of controlled studies to guide individual therapeutic decisions, our findings show that PFO closure can be done safely and may be considered to avoid recurrence in selected patients with long life expectancy and presumed paradoxic embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 16 publications
1
68
0
3
Order By: Relevance
“…It is noteworthy that these patients were considered at high risk because of a "large" shunt or multiple ischaemic lesions. In the initial experience with surgical closure, Devuyst et al reported no recurrent event in 32 patients [22], but papers by Homma et al (19.5% recurrence rate at 13 months) and the Mayo Clinic (7.5% at 1 year and 16.6% at 4 years) were disappointing [23,24]. Surgery has been superseded by the percutaneous transcatheteral approach due to the absence of open-heart surgery [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that these patients were considered at high risk because of a "large" shunt or multiple ischaemic lesions. In the initial experience with surgical closure, Devuyst et al reported no recurrent event in 32 patients [22], but papers by Homma et al (19.5% recurrence rate at 13 months) and the Mayo Clinic (7.5% at 1 year and 16.6% at 4 years) were disappointing [23,24]. Surgery has been superseded by the percutaneous transcatheteral approach due to the absence of open-heart surgery [25].…”
Section: Discussionmentioning
confidence: 99%
“…With a mean follow-up time of 19 months, we saw 4 neurological events, all in patients Ն45 years old. 12 Devuyst et al 13 11 reported on 63 patients followed up for 2.6 years with 4 recurrent neurological events. Reasons for recurrent ischemic events after either surgical or percutaneous PFO closure remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term follow-up of patients having suffered a stroke by paradoxical embolism and treated by shunt closure is scarce and inconclusive. 27,28 The role of shunts demonstrated only during TCD for clinically manifest paradoxical embolism is unknown and requires further research. Anticoagulation would minimize thrombus formation and thus embolization through cardiac and noncardiac shunts.…”
Section: Discussionmentioning
confidence: 99%